2019
DOI: 10.1136/bmjgh-2019-001517
|View full text |Cite
|
Sign up to set email alerts
|

Towards universal health coverage: advancing the development and use of traditional medicines in Africa

Abstract: African traditional medicine (ATM) and traditional health practitioners (THPs) could make significant contributions to the attainment of universal health coverage (UHC). Consequently, the WHO provided technical tools to assist African countries to develop ATM as a significant component of healthcare. Many African countries adopted the WHO tools after appropriate modifications to advance research and development (R&D) of ATM. An analysis of the extent of this development was undertaken through a survey of 47 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 16 publications
(17 reference statements)
0
54
0
4
Order By: Relevance
“…A large segment of the population in sub-Saharan Africa turns to the traditional sector when ill. Relatedly, advances in research on traditional medicines implore us to forge meaningful partnerships with the traditional medicine sector for better health outcomes. Kasilo et al 15 trace advances in research, product development, integration of traditional medicines into health system, as well as regulatory practices for traditional health practitioners. They highlight important considerations necessary to maximise the potential of this sector for UHC.…”
mentioning
confidence: 99%
“…A large segment of the population in sub-Saharan Africa turns to the traditional sector when ill. Relatedly, advances in research on traditional medicines implore us to forge meaningful partnerships with the traditional medicine sector for better health outcomes. Kasilo et al 15 trace advances in research, product development, integration of traditional medicines into health system, as well as regulatory practices for traditional health practitioners. They highlight important considerations necessary to maximise the potential of this sector for UHC.…”
mentioning
confidence: 99%
“…Nemutandani, Hendricks, and Mulaudzi (2016) found that BHPs were not ready to work with AIHPs, citing challenges of quality of health care, differences regarding concept of sciences and source of knowledge, and a lack of a policy on collaboration. Kasilo et al (2016) further indicate that AIHPs' beliefs and practices have no scientific basis and that they pose a danger to patients' health; hence they are regarded as inferior, illiterate, and unscientific by BHPs (Van Rooyen et al 2015). Lampiao, Chisaka, and Clements (2019) indicate that the consulting of AIHPs led to a delay in patients seeking treatment and consulting BHPs.…”
Section: Discussionmentioning
confidence: 99%
“…Field observation showed that the nursery (Figure 1) has more than 200 tree species that are crucial to people's everyday health needs. Traditional medicines have been found to have a considerable role in the achievement of SDG 3 on Good Health [58][59][60]. Traditional medicines can offset some of the challenges faced by rural and poor communities in accessing health in South Africa, which is often beyond the reach of many.…”
Section: Kruger National Park's Contribution To Health- Food-and Education-related Sdgsmentioning
confidence: 99%